Pengembangan Media Apron Sistem Pencernaan Manusia untuk Siswa Tunarungu - Uswatun Khasanah; Ahmad Samawi (Jurnal ORTOPEDAGOGIA, 2018)
Hasil observasi tentang pembelajaran IPA kelas VIII SMPLB, materi paling sulit dipahami adalah sistem pencernaan, dikarenakan guru memiliki keterbatasan media. Tujuan penelitian menghasilkan produk media Apron Sistem Pencernaan Manusia untuk siswa tunarungu kelas VIII SMPLB. Penelitian menggunakan metode pengembangan model Borg and Gall. Data yang digunakan kualitatif dan kuantitatif. Pengumpulan data menggunakan angket dan tes. Teknik analisis data meliputi deskriptif kualitatif dan kuantitatif. Hasil penelitian menunjukkan media layak digunakan siswa tunarungu kelas VIII SMPLB. Kesimpulan dari penelitian media Apron Sistem Pencernaan Manusia berhasil dikembangkan. Saran bagi guru dianjurkan menggunakan media apron, bagi peneliti selanjutnya disarankan mengembangkan media pada materi lain.From the observations of science teaching in class VIII SMPLB, the material most difficult to understand is the digestive system. That is because teachers have limited media. The purpose of this research and development was to produce products an Apron media of Human Digestive System for students with hearing impairment class VIII in SMPLB. This research method was adapted from Borg and Gall development model. The type of data was obtained by the qualitative and quantitative data. The collection of data was obtained using questionnaires and tests. Data analysis techniques was including qualitative and quantitative descriptive analysis. The result of this research was media well-used for students with hearing impairment of class VIII in SMPLB. The conclusion of this study media Apron Human Digestive System for deaf students of class VIII SMPLB has been successfully developed. Suggestions for teachers are encouraged to use apron media, for further research is suggested to develop media on other materials.